Iodine Staining of Escherichia coli Expressing Genes Involved in the Synthesis of Bacterial Glycogen - Demonte, Ana M. (2014)
The presence of intracellular glycogen can be detected by the following iodine staining technique. Cells with glycogen stain dark brown, whereas in its absence they remain with a pale yellowish color. It is hypothesized that iodine atoms fit into helical coils formed by the α-polyglucan to form a coloured glycogen-iodine complex. Here, we have studied the expression of Streptococcus mutans (S. mutans) genes that control the biosynthesis of this polysaccharide. Thus, we expressed glgC and glgD genes coding for both ADP-Glc pyrophosphorylase subunits in Escherichia coli (E. coli) AC70R1-504 cells to complement the deficient accumulation of glycogen by this strain. In control cells or in those where an inactive protein was expressed, the synthesis of the polysaccharide was undetectable by this iodine staining technique.